Latent heat loss of dairy cows in an equatorial semi-arid environment - da Silva, Roberto Gomes; Campos Maia, Alex Sandro [UNESP]; de Macedo Costa, Leonardo Lelis; Fernandes de Queiroz, Joao Paulo A. (Springer, 2012)
The present study aimed to evaluate evaporative heat transfer of dairy cows bred in a hot semi-arid environment. Cutaneous (E (S)) and respiratory (E (R)) evaporation were measured (810 observations) in 177 purebred and crossbred Holstein cows from five herds located in the equatorial semi-arid region, and one herd in the subtropical region of Brazil. Rectal temperature (T (R)), hair coat surface temperature (T (S)) and respiratory rate (F (R)) were also measured. Observations were made in the subtropical region from August to December, and in the semi-arid region from April to July. Measurements were done from 1100 to 1600 hours, after cows remained in a pen exposed to the sun. Environmental variables measured in the same locations as the animals were black globe temperature (T (G)), air temperature (T (A)), wind speed (U), and partial air vapour pressure (P (V)). Data were analysed by mixed models, using the least squares method. Results showed that average E (S) and E (R) were higher in the semi-arid region (117.2 W m(-2) and 44.0 W m(-2), respectively) than in the subtropical region (85.2 W m(-2) and 30.2 W m(-2), respectively). Herds and individual cows were significant effects (P < 0.01) for all traits in the semi-arid region. Body parts did not affect T (S) and E (S) in the subtropical region, but was a significant effect (P < 0.01) in the semi-arid region. The average flank T (S) (42.8A degrees C) was higher than that of the neck and hindquarters (39.8A degrees C and 41.6A degrees C, respectively). Average E (S) was higher in the neck (133.3 W m(-2)) than in the flank (116.2 W m(-2)) and hindquarters (98.6 W m(-2)). Coat colour affected significantly both T (S) and E (S) (P < 0.01). Black coats had higher T (S) and E (S) in the semi-arid region (41.7A degrees C and 117.2 W m(-2), respectively) than white coats (37.2A degrees C and 106.7 W m(-2), respectively). Rectal temperatures were almost the same in both subtropical and semi-arid regions. The results highlight the need for improved management methods specific for semi-arid regions.
Keywords: Dairy cows; Thermoregulation; cutaneous evaporation; Respiratory evaporation; tropical environment; Semi-arid